The giant tear of retinal pigment epithelium following focal laser in central serous chorioretinopathy - Oli, Avadhesh (Rom J Ophthalmol, 2020)
A 35-year-old male smoker presented with reduced vision in OD for the previous two years. He reported a further drop in the vision for the previous two weeks after he underwent focal laser elsewhere. Clinical examination and multimodal imaging confirmed a giant tear of the retinal pigment epithelium (RPE) and a focal leak of CSCR. He was managed with the focal laser to the active leak and lifestyle modification. The ocular condition remained stable. RPE rips in CSCR have been reported to occur spontaneously or with an intervention like exogenous use of steroids, or photodynamic therapy (PDT). This case highlighted the fact that focal laser can precipitate RPE rip in a case of CSCR with tense bullous PED. The physician should keep this fact in mind while counselling the patient before a laser procedure and suspect an RPE rip in a patient with CSCR who presents with an acute onset of vision loss.